2020
DOI: 10.1097/bpb.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Valgus slipped capital femoral epiphysis: presentation, treatment, and clinical outcomes using patient-reported measurements

Abstract: Valgus slipped capital femoral epiphysis (SCFE), is rare. This study describes the diagnosis, treatment and outcome of valgus SCFE in Uruguay. The medical records and radiographs were reviewed in eight consecutive children [mean age 11.9 years (range 9–13; six female)] with valgus SCFE between 1997–2017. In 2018–2019, all patients were reexamined clinically, new radiographs obtained, and patient-reported outcomes completed using the international tool of hip results (iHOT-12). The prevalence of clinical femoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Gelink et al reported on a small case series of 8 patients with valgus SCFE: 2/8 presented as bilateral slips, 1 patient subsequently developed a contralateral slip, and all of the patients were thought to have idiopathic SCFE. 52 A larger metanalysis found that 31% of valgus SCFE patients (23/74) initially presented as a bilateral SCFE, which is higher than the rate of 18% that has been reported for idiopathic SCFE. 9,53 While valgus slips represent an uncommon subset of SCFE, with about 100 reported cases in the literature, their unique radiographic characteristics make it important for us to identify them.…”
Section: Valgus Scfementioning
confidence: 87%
“…Gelink et al reported on a small case series of 8 patients with valgus SCFE: 2/8 presented as bilateral slips, 1 patient subsequently developed a contralateral slip, and all of the patients were thought to have idiopathic SCFE. 52 A larger metanalysis found that 31% of valgus SCFE patients (23/74) initially presented as a bilateral SCFE, which is higher than the rate of 18% that has been reported for idiopathic SCFE. 9,53 While valgus slips represent an uncommon subset of SCFE, with about 100 reported cases in the literature, their unique radiographic characteristics make it important for us to identify them.…”
Section: Valgus Scfementioning
confidence: 87%
“…In an earlier study, spanning 1998 through 2003 from our institution [ 29 ], four patients with seven valgus SCFEs were described, and all were Black. In a recent study for Uruguay of eight children with valgus SCFEs [ 5 ], seven of the eight were White, and one was Black (Gelink A—personal communication). Segal et al [ 4 ] described patients with valgus SCFE; one was Hispanic, and one was Black.…”
Section: Discussionmentioning
confidence: 99%
“…Slipped capital femoral epiphysis (SCFE) can be divided into idiopathic and atypical types [ 1 , 2 ], with idiopathic being more common [ 1 ]. Most SCFEs demonstrate a varus deformity, although valgus types do exist [ 3 , 4 , 5 ]. The typical SCFE demonstrates an inferior displacement of the epiphysis relative to the metaphysis on radiographs, thus a varus deformity; however, a few may demonstrate a superior displacement of the epiphysis relative to the metaphysis on radiographs, or a valgus deformity.…”
Section: Introductionmentioning
confidence: 99%
“…Slipped capital femoral epiphysis (SCFE) in humans is characterized clinically as an epiphyseal posteromedial displacement relative to the metaphysis (Khaladkar, Sherawat, et al, 2015; Tayton, 2007). In a small fraction of cases there is a posterolateral displacement of the epiphysis relative to the metaphysis (Gelink, Cúneo, et al, 2021). Torsion has been reported as an etiologic factor in initial slips (Aronson & Tursky, 1996).…”
Section: Discussionmentioning
confidence: 99%